Ensuring the principle of zero tolerance to antisocial manifestations: The important condition of the constitutional state creation - Talgat Akimzhanov, Talgat; Suleymenova, Saule; Altynbekkyzy, Alua; Zinkevich, Tatyana; Edressov, Serik; Dosanova, Meruert (Opción, 2018)
Article is devoted to relevant and practically significant problem. Ensuring the principle of zero tolerance to any antisocial manifestations gives the chance to look at the general system of crime prevention in general. The term Zero Tolerance has develop a familiar feature of the crime control landscape. In new times it has been organized regularly by police managers, politicians, policy-makers and media. The novelty of this approach of counteracting crime is to gain the opportunity to improve the effectiveness of existing forms and prevention methods and also will allow finding the new directions of activity, previously unknown to law enforcement practice.